The growth of commercial establishments and its implications on the urban residential space (District 4, Zone 54, Barangay 552, Sampaloc, Manila) - Elardo, Sheila Valencia (Quezon City College of Architecture, University of the Philippines Diliman, 2008)
This is a study on the commercial activity and its effect and implications to the uses of residential space. The study traces the commercial growth and retail activities in Manila from their roots to the present times. It shows the spread of commerce in the chosen area particularly Barangay 552, District 4 in Sampaloc, Manila. More importantly, the study tries to explain how commercialization has altered the functional morphology of the houses in the district. Several techniques of gathering data were applied in the study. It used surveys, semi-structured interview with the residents of Barangay 552, Sampaloc, Manila, personal observations, and comparisons of the two kinds of houses namely the long stretch and sprawled houses with commercial space. Questions for both interview and written questionnaires revolve around the respondent's response to the change of houses, their needs and satisfaction to achieve space. The study found out that improvement for commercial and personal use, household growth and extension of spaces are the nature of the changes in houses. Modifications of houses are based on the residents needs at present. Extensions, flexibility, dividing and contracting, converting, renovating and improvement, vertical expansions are the implications of the changes inn use of space. By employing the nature of synthesis through architectural programming process, the four considerations (form, economy, function and time) help simplify the obtained data of the study. This can serve as reference tool for residents and guide for probable house improvements, and design tools for designers, developers and planners of urban residential projects, even academicians involved in research activities of urban residential with commercial spaces.
Vita.
Thesis (Master of Architecture)--University of the Philippines, Diliman.
Keywords: Commercial spaces -- Sampaloc (Manila).; Dwellings -- Sampaloc (Manila).